2008
DOI: 10.4028/www.scientific.net/msf.587-588.862
|View full text |Cite
|
Sign up to set email alerts
|

Copper Slag Mortar Properties

Abstract: Copper slag is a copper industry waste that is essentially used as an abrasive for metals to remove coatings or paintings, due to its hardness, sieve distribution and rough surface, mainly in the naval industry. After the wearing process, copper slag retains most of its original properties, and remaining an environmental problem. Chemical composition of copper slag presents a high Fe, Si and Al oxide content what makes it a pozzolanic material. Thus, it is possible to use it as a partial replacement for sand a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
(6 reference statements)
1
14
0
Order By: Relevance
“…AlJabri et al, 2006AlJabri et al, , 2009aAlJabri et al, , 2009bAlJabri et al, , 2011Alnuaimi, 2009;Bahadur and Nayak, 2012;Nagan, 2010, 2011;Brindha and Sureshkumar, 2010;Cachim et al, 2009;Ghosh, 2007;Holcim (Singapore), 2007;Hwang and Laiw, 1989;Ishimaru et al, 2005;Koh and Lye, 2012;Lee et al, 2003;Ling and Thim, 1999;Madany et al, 1991;Meenakashi and Ilangovan, 2011;Nazer et al, 2013;Resende et al, 2008;Shoya et al, 1997Shoya et al, , 1999Shoya et al, , 2003Song et al, 2003;Sudarvizhi and Ilangovan, 2012;Wu et al, 2010a) is that, even though the researchers did not generally comply with the important requirement of maintaining the particle grading when CS/WCS was used as a component of sand, Table 4. A series of trial mixes, using SIBA, RCA and CS/WCS materials the material can be used effectively for making concrete, provided that good concrete design practice is adopted.…”
Section: Strengthmentioning
confidence: 96%
“…AlJabri et al, 2006AlJabri et al, , 2009aAlJabri et al, , 2009bAlJabri et al, , 2011Alnuaimi, 2009;Bahadur and Nayak, 2012;Nagan, 2010, 2011;Brindha and Sureshkumar, 2010;Cachim et al, 2009;Ghosh, 2007;Holcim (Singapore), 2007;Hwang and Laiw, 1989;Ishimaru et al, 2005;Koh and Lye, 2012;Lee et al, 2003;Ling and Thim, 1999;Madany et al, 1991;Meenakashi and Ilangovan, 2011;Nazer et al, 2013;Resende et al, 2008;Shoya et al, 1997Shoya et al, , 1999Shoya et al, , 2003Song et al, 2003;Sudarvizhi and Ilangovan, 2012;Wu et al, 2010a) is that, even though the researchers did not generally comply with the important requirement of maintaining the particle grading when CS/WCS was used as a component of sand, Table 4. A series of trial mixes, using SIBA, RCA and CS/WCS materials the material can be used effectively for making concrete, provided that good concrete design practice is adopted.…”
Section: Strengthmentioning
confidence: 96%
“…However, experiences on the usage of these residuals in many sectors of production have been carried out, with very good published results, particularly on the usage of copper slag in the construction industry. This residual has been used as raw material in cement production, as a substitute for arid, both in concrete and cement mortars (Zain et al (2004), Goñi et al (1994), Resende et al (2008), Al-Jabri et al (2006), Shi et al (2008), Wu et al(2010a), Wu et al(2010b), Moura et al (1999)). Mortar is a material regularly used as both decorative coating or as a means of waterproofing of surfaces, and as a merger of prefabricated cement elements and clay bricks in building work.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it is fluid, which after a period of cement and water reactivity, acquires resistance until its final hardening. On the other hand, copper slag have also been used as raw material for the polishing and cleaning by abrasive blast of metallic structures (Kambham et al, 2007), (Resende et al 2008) and as gravel in road work (Douglas & Mainwaring, 1985), among other commercial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resende et al [6] reported a small reduction in concrete compressive and flexural strengths due to substitution of natural sand by copper slag. Workability was also reduced, although it stayed within reasonable limits.…”
Section: Introductionmentioning
confidence: 99%